2005
DOI: 10.1080/02687030500166957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapy targeted at verb retrieval and the realisation of the predicate argument structure: A case study

Abstract: Background: Verb retrieval and sentence production difficulties are both common features of aphasia. Previous treatment studies have focused predominantly on verb retrieval and the mapping of semantic and syntactic structure. There have been more limited investigations of the production of the predicate argument structure (PAS). Aims: This study aimed to evaluate the outcome of intensive therapy for a client with aphasia. NS had multiple and interacting difficulties that resulted in problems in producing sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
56
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 22 publications
(25 reference statements)
5
56
0
2
Order By: Relevance
“…However, an increasing number of investigations have addressed treatment of verb retrieval [5][6][7][8][9]. Targeting verb retrieval is potentially an important component of aphasia rehabilitation because verbs not only carry critical meaning but also have important functions in the structural formulation of sentences [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, an increasing number of investigations have addressed treatment of verb retrieval [5][6][7][8][9]. Targeting verb retrieval is potentially an important component of aphasia rehabilitation because verbs not only carry critical meaning but also have important functions in the structural formulation of sentences [10].…”
Section: Introductionmentioning
confidence: 99%
“…In aphasia that knowledge may be damaged, and therapy therefore needs to target the damaged syntactic components, not just the verbs' phonological or semantic properties. Jones (1986) and Webster et al (2005) treated verbs and their argument structures, and found generalization to narrative speech. It is feasible that a similar approach targeting nouns and their syntax will also yield positive results.…”
Section: Alternatives To Lexical Therapymentioning
confidence: 99%
“…Byng et al, 1994;Fink et al, 1992;Jones, 1986;Webster et al, 2005). The approach assumes a close relationship between the semantic and syntactic properties of a verb.…”
Section: Alternatives To Lexical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these showed an increase in verb retrieval abilities after training (Linebaugh, Baron, & Corcoran, 1998;McNeil, Doyle, Spencer, Goda, Flores, & Small, 1998;Raymer & Ellsworth, 2002;Wambaugh, Doyle, Martinez, & Kalinyak-Fliszar, 2002;Webster & Morris, 2005; see also Rodriguez, Raymer, & Gonzalez-Rothi, 2006 this issue), although generalisation to untreated items was not always found. In some participants better sentence production was reported after verb production training.…”
mentioning
confidence: 99%